2022
DOI: 10.1038/s41598-021-04316-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival, treatment regimens and medical costs of women newly diagnosed with metastatic triple-negative breast cancer

Abstract: Individuals diagnosed with metastatic triple-negative breast cancer (mTNBC) suffer worse survival rates than their metastatic non-TNBC counterparts. There is little information on survival, treatment patterns, and medical costs of mTNBC patients in Asia. Therefore, this study aimed to examine 5-year survival, regimens of first-line systemic therapy, and healthcare costs of mTNBC patients in Taiwan. Adult females newly diagnosed with TNBC and non-TNBC as well as their survival data, treatment regimens and costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
(61 reference statements)
1
29
0
Order By: Relevance
“…25 In Western countries (United States, Canada and Germany) 65-67% of mTNBC patients receive monotherapy as their first-line treatment rather than combination regimens, which are more popular in Asia. 26 However, the overall efficacy of both monotherapy and combined chemotherapy for the treatment of mTNBC is limited. A meta-analysis of mTNBC subgroups from three Phase III first-line trials reported a pooled median ORR of 23%, OS of 17.5 months and median PFS of 5.4 months with single-agent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…25 In Western countries (United States, Canada and Germany) 65-67% of mTNBC patients receive monotherapy as their first-line treatment rather than combination regimens, which are more popular in Asia. 26 However, the overall efficacy of both monotherapy and combined chemotherapy for the treatment of mTNBC is limited. A meta-analysis of mTNBC subgroups from three Phase III first-line trials reported a pooled median ORR of 23%, OS of 17.5 months and median PFS of 5.4 months with single-agent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of predictive value for the HER2 enriched subtype in presented results could therefore stem from the relatively low number of identified cases with this subtype ( n = 15; 5% of all tumors). Triple negative breast cancers (TNBC) are known to lead to a poor prognosis, with reported overall 5-year survival rates between 62% and 82%, compared to 75% to 86% in the case of non-TNBC patients [ 54 , 55 ]. Our results agree with the survival rates of TNBC patients, the data analyzed here yielding a 5-year survival rate of 61% ( Supplementary Figure S1C ).…”
Section: Discussionmentioning
confidence: 99%
“…TNBC patients have a very poor prognosis overall, and survival rarely extends beyond 12 months from the time of recurrence. The 5-year overall survival rate in metastatic TNBC (mTNBC) patients is 4–20%, much worse than the other types of breast cancer [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%